Application of metagenomic next-generation sequencing in cutaneous tuberculosis - Kong, Min; Li, Wei; Kong, Qingsheng; Dong, Haixin; Han, Aizhong; Jiang, Liqing (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculous infection in a skin wound is a rare but well-known condition. Herein, this study involved a child infected with tuberculosis after cutting. Due to swelling and pain in the wrist tissue, he was admitted to Affiliated Hospital of Jining Medical University of Shandong Province on October 16th, 2021. His medical history recorded only a wound. He was discharged after debridement. Laboratory datas were normal. Two months after the surgery, his wound was still swelling and pain. Secretions from the wound were again sent for mNGS. mNGS was only given to three reads of the M. tuberculosis complex group (MTBC). A diagnosis of cutaneous tuberculosis was made. Wound disappeared when anti-tuberculosis was administered. From this case, tuberculosis presenting as severe cutaneous wound is rare but should be considered in clinical diagnosis. Clinicians should also pay enough attention for extrapulmonary infection with MTBC in patients, particularly some long-suffering patients, and finded out specific pathogen as soon as possible. mNGS maybe help identify pathogens and treat them early in the future, which can improve prognosis.